2017
DOI: 10.22159/ajpcr.2017.v10s1.20512
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy Image Classification Using Deep Neural Network

Abstract: Healthcare is an important field where image classification has an excellent value. An alarming healthcare problem recognized by the WHO that the world suffers is diabetic retinopathy (DR). DR is a global epidemic which leads to the vision loss. Diagnosing the disease using fundus images is a timeconsuming task and needs experience clinicians to detect the small changes. Here, we are proposing an approach to diagnose the DR and its severity levels from fundus images using convolutional neural network algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This study focuses on analyzing classification methods to detect these three pathologies using medical imaging [10] [11]. Recent advances have shown that deep learning algorithms, particularly using optical coherence tomography (OCT) [12], [13], [14] and fundus images [15], [16], can automatically extract pathological features. Furthermore, features identified in one pathology may be applicable to others, allowing for efficient classification across multiple conditions [17].…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on analyzing classification methods to detect these three pathologies using medical imaging [10] [11]. Recent advances have shown that deep learning algorithms, particularly using optical coherence tomography (OCT) [12], [13], [14] and fundus images [15], [16], can automatically extract pathological features. Furthermore, features identified in one pathology may be applicable to others, allowing for efficient classification across multiple conditions [17].…”
Section: Introductionmentioning
confidence: 99%